Pengelolaan Wisata Halal Di Situs Guha Jepang Gampong Blang Panyang Kota Lhokseumawe Aceh - Bobby Rahman; Rasyidin Rasyidin; Teuku Muzaffarsyah; Zulhilmi Zulhilmi (Indonesian Community Service and Empowerment Journal (IComSE), 2021)
The purpose of this service is to realize community service planning conducted with Forum Group Discussion (FGD) in Gampong Balang Panyang with Gampong Leadership, Tuha Peut and other youth figures and Stake holders. There are several problems behind this devotion, namely the management of tourism things have not been managed properly in accordance with Islamic law, the method of Devotion Activities is based on the principle of participatory towards all parties involved. Planning together, conducting activities, monitoring and evaluating together the extent of the progress of the activities. As a result, This Japanese Guha tourist site can also be a means of education as well as an additional literacy about the history of the past. Of course, this becomes a picture that the management must be maximized and the development to all citizens in developing halal tourism potential in the historical site. in conclusion, the management of Guha Japan Tourism Site became the authority of the Lhokseumawe City Government through the Tourism Office and the Education and Culture Office. This makes the management of Japan Guha tourism has not been maximized.